Environmental Soil Phosphorus Threshold under No-Tillage and Swine Manure Application - Bousfield,Sérgio Walace (2020)
Abstract Swine manure is applied in agricultural fields as a source of nutrients for plant growth, however, excessive application over the years can promote soil phosphorus (P) accumulation. The objective of this study was to establish the environmental soil P threshold based on the degree of P saturation (DPS), as well, to evaluate the soil P storage capacity. The experiment was carried out in an Oxisol (sandy clay loam texture), under no-tillage and crop rotation. Treatments consisted of four annual doses of liquid swine manure (0, 100, 200, and 300 m3 ha-1 year-1), and three doses of mineral fertilizer (0, 50, and 100% of the crop nutrients requirement), in a randomized block with split-plot design (four replications). Soil P content was analyzed by PMehlich-1, PCaCl2, water-soluble P (WSP) and total P. The application of swine manure and mineral fertilizer increased soil P contents mainly at 0-10 cm depth. The DPS corresponding to the change point was 14.9% at depth 0-10 and 8.6% at depth 0-20 cm with WSP and 18.7% at 0-10 cm and 8.9% at 0-20 cm depth with PCaCl2. The lowest change point value was DPS 8.6% which corresponds to 43 mg kg-1 of PMehlich-1, so, in practical terms, we suggest this value as the environmental soil P threshold. The soil P storage capacity indicated negative values with the higher doses of swine manure and mineral fertilizer which increases the vulnerability of P loss by surface and subsurface hydrological transfer pathway.